Strategi Pemenuhan Ruang Terbuka Hijau (RTH) di Kecamatan Panakkukang Kota Makassar - Nurhafifa; Ruslan, Rusneni; Abbas, Jamilah; AS, Kurniati (Fakultas Teknik Universitas Bosowa, 2023)
Abstract. The purpose of this study is to calculate the area of availability and need for Green Open Space (RTH) in Panakkukang District, Makassar City, and formulate a strategy for fulfilling Green Open Space in Panakkukang District, Makassar City. This research is qualitative research that is interpreted descriptively. The data obtained were then analyzed using qualitative analysis using the Indonesian Green-Blue Index (IHBI) method and descriptive analysis. (1) The results of the analysis obtained from calculating the area of green open space needs based on the area and population in Panakkukang District have been met to reach 30%, by looking at the results of calculating the area of availability of green open space using the Indonesian Green-Blue Index method, which is 668.10 Ha with a percentage of 39.2% of the area of Panakkukang District. (2) The strategy of fulfilling green open space in Panakkukang District is to maintain and maintain the preservation of existing green open space by meeting the criteria for the Green Open Space function consisting of ecological, water catchment, economic, socio-cultural, and disaster management functions.